Dinoxyleborus Smith, a new genus of Neotropical xyleborine ambrosia beetle (Coleoptera, Curculionidae: Scolytinae) - Smith, Sarah M. (Zootaxa, 2017)
An ongoing review of Neotropical Xyleborini (Coleoptera, Curculionidae, Scolytinae) has revealed a new genus, Dinoxyleborus gen. nov. (type species Dinoxyleborus cognatoi sp. nov.), from South America. Two new species are described and one new combination is proposed: Dinoxyleborus cognatoi, sp. nov., D. infernus sp. nov., and D. sexnotatus (Schedl), 1970. A modification of Wood’s 2007 key to Neotropical Xyleborini genera and a key to Dinoxyleborus species are given.